Isim Fa’il dalam Kitab Nurul Burhan (Analisis Shorof) - Miftahul Mufid; Nilna Indriana; Ahmad Amirul Kholid (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2023)
Abstract: Language is a medium that is only owned by humans in conveying an idea, idea, or feeling to others. For Muslims living in Indonesia, learning Arabic is very important because in practice the Muslim community cannot be separated from the Arabic text. One of the books of Manaqib that are often used as a means of joint prayer is the Book of Manaqib Nurul Burhani. From here the researcher will discuss isim fa'il in the book Nurul Burhan and focus on discussing the form of wazan. This research uses descriptive qualitative methods with library research techniques. The results of this study show that Isim Fa'il contained in the book of Nurul Burhan as many as 86 words spread in Maqro '1, 2, 3, 4, 5, 6, and 7, among which some are formed from wazan mujarrod and mazid.